Study protocol for a randomised trial evaluating the non-inferiority of stepped palliative care versus early integrated palliative care for patients with advanced lung cancer. Issue 2 (10th February 2022) - Post, Kathryn E; Heuer, Lauren B; Kamal, Arif H; Kumar, Pallavi; Elyze, Madeleine; Griffith, Sarah; Han, Jacqueline; Friedman, Fred; Jackson, Ashley; Trotter, Chardria; Plotke, Rachel; Vyas, Charu; et al.
Abstract : Introduction: Integrating palliative care (PC) early in the illness course for patients with serious cancers improves their outcomes and is recommended by national organisations such as the American Society of Clinical Oncology. However, monthly visits with PC clinicians from the time of diagnosis can be challenging to implement due to the lack of specialty-trained PC clinicians and resources. Therefore, we developed a stepped care model to triage PC service based on patients' needs. Methods and analysis: We are conducting a non-blinded, randomised trial to evaluate the non-inferiority of a stepped PC model compared with an early integrated PC model for improving patients' quality of life (QOL) at 24 weeks (primary outcome). Patients assigned to early integrated PC meet with PC every 4 weeks throughout their illness. Patients assigned to stepped PC have PC visits only at clinically significant points in their illness (eg, cancer progression) unless their QOL decreases, at which time they are 'stepped up' and meet with PC every 4 weeks throughout the remainder of their illness. Secondary aims include assessing whether stepped PC is non-inferior to early integrated PC regarding patient-clinician communication about end of life care and length of stay on hospice as well as comparing resource utilisation. Patients are recruited from the Massachusetts General Hospital Cancer Center, Boston, Massachusetts; Duke Cancer Center, Durham, North Carolina and University of Pennsylvania Abramson Cancer Center, Philadelphia, Pennsylvania. The target sample size is 510 patients. Ethics and dissemination: The study is funded by the National Cancer Institute, approved by the Dana-Farber/Harvard Cancer Center Institutional Review Board and will be reported in accordance with the Consolidated Standards of Reporting Trials statement. We will disseminate results through professional society meetings, peer-reviewed publications and presentations to patient organisations. Trial registration number: NCT03337399 .